If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = 4(x + 5) + 9 Reorder the terms: 1 + 5x = 4(x + 5) + 9 Reorder the terms: 1 + 5x = 4(5 + x) + 9 1 + 5x = (5 * 4 + x * 4) + 9 1 + 5x = (20 + 4x) + 9 Reorder the terms: 1 + 5x = 20 + 9 + 4x Combine like terms: 20 + 9 = 29 1 + 5x = 29 + 4x Solving 1 + 5x = 29 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + 5x + -4x = 29 + 4x + -4x Combine like terms: 5x + -4x = 1x 1 + 1x = 29 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + 1x = 29 + 0 1 + 1x = 29 Add '-1' to each side of the equation. 1 + -1 + 1x = 29 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 29 + -1 1x = 29 + -1 Combine like terms: 29 + -1 = 28 1x = 28 Divide each side by '1'. x = 28 Simplifying x = 28
| 8(x-11)-6=20x-190 | | 20+-25= | | -2(9n+4)=22-7n | | h^2-3h+c=0 | | 4m^2+2n=3 | | 6x+8-13x+10=x+6+x+3x | | -5g=g-h | | 2(3c-1)-4=4c+8 | | (3d+6)(4d-11)=0 | | 10x+3x-4= | | 12x-3x+6x+5x= | | 2x(x+5)=870 | | 5y=4y^2-6 | | 2x^2-20x-44=0 | | 6c^2-11c+3=0 | | x^5-789=0 | | 2x+3x-3+10=4x+14 | | 6x+6=-112-10x | | 12x^4+12x^3-9x^2+16x-4=0 | | 27=0.428x | | 7x+3x-4x+11=7x+17-4x | | 6x^2=2x+2 | | 6(3x+3)=-198 | | -10=0.8y+6 | | -5x+4=-3x-2 | | 6x-3+2x=-67 | | 6x-3+2x=-64 | | 4(6x+2)=-112 | | -6x+1=5x+45 | | -23=3x+x+1 | | -7x-8=-1 | | 6(2x-1)=8x-2 |